Performance of a whole tree mechanised timber harvesting system when clear-felling a 32-year-old pinus taeda l. Stand - Pitz N.O.* (2021)
© The Author(s). 2021 Open Access.Background: Work studies are fundamental for the development and assessment of timber harvesting systems aimed at rationalising and improving forest management activities. Methods: This study evaluated the operational performance of a mechanised whole-tree harvesting system in 32-year-old Pinus taeda L. stands producing multiple timber products. A time and motion study at the cycle element level was conducted to evaluate the operational performance of each component of the harvesting system. Equations were developed to estimate the productivity of tree extraction activity with a wheeled skidder and log loading with a mechanical loader. Results: Tree felling with an excavator-based harvester had the highest mean productivity (135 m3 per productive machine hour), followed by tree extraction with a wheeled skidder (117 m3 per productive machine hour), while manually processing larger logs with a chainsaw had the lowest productivity (25.7 m3 per productive machine hour). Operator, extraction distance and mean log volume had a significant effect on the performance of different activities and were included in productivity models. Conclusions: Operational performance of equipment was variable and dependent on the effect of the operator, extraction distance and log volume. Thus, the use of models to estimate productivity considering such factors, coupled with reduced delays to increase utilisation of equipment, will contribute to the better management and planning of forest harvesting operations under the evaluated conditions.